Electrocorticography Arrays: Incorporation of Silicon Carbide and Diamond‐Like Carbon as Adhesion Promoters Improves In Vitro and In Vivo Stability of Thin‐Film Glassy Carbon Electrocorticography Arrays (Adv. Biosys. 1/2018). Issue 1 (16th January 2018) - Vomero, Maria; Castagnola, Elisa; Ordonez, Juan S.; Carli, Stefano; Zucchini, Elena; Maggiolini, Emma; Gueli, Calogero; Goshi, Noah; Ciarpella, Francesca; Cea, Claudia; Fadiga, Luciano; Ricci, Davide; et al.
Abstract : In article number1700081, Maria Vomero and co‐workers show that the incorporation of silicon carbide and diamond‐like carbon as adhesion promoters between glassy carbon (GC) electrodes and polyimide and between GC and platinum traces greatly improves both in vitro and in vivo stability of GC electrocorticography (ECoG) arrays. The devices undergo chemically induced oxidative stress and electrical stimulation without delaminating and failing. After chronic implants, no sign of severe immune reaction is shown.